Comparative Evaluation of Structural and Functional Changes in Periodontal Tissues of Protested Teeth with Metal-Ceramic Prostheses (Eurasian Medical Research Periodical, 2022)
To increase the efficiency of prosthetics, the use of metal, metal-ceramic and zircon dentures was determined. The issues of modern methods of dental prosthetics are highlighted. The analysis of the most common errors and complications in prosthetics with the use of fixed structures has been carried out. The assessment of the physical and technical properties of cermet structures remains poorly studied. To exclude ceramic chips, antagonizing dentures are not brought to contact, which can lead to deformation. Thus, the question of the influence of fixed prostheses on the clinical and morphological state in the absence of periodontal tissues remains unstudied.